2020
DOI: 10.1038/s41598-020-73332-5
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation of the lateral cerebellar nucleus promotes neurogenesis in rats after motor cortical ischemia

Abstract: Deep brain stimulation (DBS) has been tentatively explored to promote motor recovery after stroke. Stroke could transiently activate endogenous self-repair processes, including neurogenesis in the subventricular zone (SVZ). In this regard, it is of considerable clinical interest to study whether DBS of the lateral cerebellar nucleus (LCN) could promote neurogenesis in the SVZ for functional recovery after stroke. In the present study, rats were trained on the pasta matrix reaching task and the ladder rung walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…It might be assumed that GABAergic PC efferents do not contribute to such prevention. That is why other pathways of cerebellar participation in seizure modulation might be signi cant [11,44,45]. Additionally, less marked reduction of PC at the early stage of PTZ kindling does not exclude their involvement in myoclonus pathogenesis and the facilitation of myoclonus with LCN ES.…”
Section: Discussionmentioning
confidence: 99%
“…It might be assumed that GABAergic PC efferents do not contribute to such prevention. That is why other pathways of cerebellar participation in seizure modulation might be signi cant [11,44,45]. Additionally, less marked reduction of PC at the early stage of PTZ kindling does not exclude their involvement in myoclonus pathogenesis and the facilitation of myoclonus with LCN ES.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral injury caused by transient forebrain ischemic stroke leads to cognitive dysfunctions, and this process is accompanied by elevated neurogenesis in the neurogenic niches of the postnatal brain [ 50 , 51 ]. Many studies have already been suggested that the neurogenesis, including cell proliferation and differentiation of neuroblasts into mature neurons by some stimuli, is the key role to promote neurological rehabilitation and cognitive dysfunction in some common neurodegenerative diseases, including stroke in rodents [ 52 , 53 ]. In the present study, our results demonstrated that the capability of neurogenesis in young gerbils after long-term I/R injury is directly proportional to the recovery of neurological function and cognitive ability, on the contrary, this capability of old gerbils is obviously insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…157 Sarica et al (2022) recently published their work in an ex-vivo setting regarding appropriate parameters for TUS to enhance adaptability of such applications and to not produce hazardous temperatures on DBS lead. 157 Alternatively, non-invasive stimulation 65,241,242 but also invasive 63,65,242 stimulation of the cerebellum has been tried out for post-stroke recovery. Preclinical studies proved DBS stimulation to the cerebellum for post-stroke conditions to be effective in rodents.…”
Section: Spinal Cord Stimulation (Scs)mentioning
confidence: 99%
“…Invasive approaches, especially deep brain stimulation (DBS), have been discussed for stroke recovery due to promising preclinical results suggesting their potential for neurorehabilitation in patients. 19,[61][62][63][64][65] Accordingly, a first preclinical, invasive study showed that neuromodulation of the dentate nucleus via DBS improved stroke recovery. 65 DBS of the cerebellar dentate nucleus (DN) [66][67][68] has also led to improved motor recovery, probed in a firstin-human trial (NCT02835443).…”
mentioning
confidence: 99%